Biomarkers of Temporomandibular Disorders - Dominica Dian Saraswati Sumantri; Silvia Naliani; Shelly Lelyana; Ferry Sandra (Maranatha Christian University, 2018)
Temporomandibular disorder is a disorder that includes masticatory muscles or temporomandibular joints, unbalanced joint function or both. The disorders can disturb daily activity, cause by pain. The therapy consuming time and cost. Early detection of temporomandibular disorder is needed, as a prevention of more severe disorders. Increased cortisol can be found in myofacial pain and is not found in internal dearagement or osteoarthritis. Biomarkers of interleukin and monocyte chemoattractant proteins are only found in osteoarthritis. The use of biomarkers can be useful in detecting temporomandibular disorders. Biomarkers can be measured from blood, serum and saliva. Cortisol, dopamine and TAC are potential biomarkers in the temporomandibular disorder.